Traditional Expressions as a Source of Local Wisdom - Sarman, Sarman (ALAYASASTRA, 2017)
Traditional expressions is one of folklore verbal that need to be preserved. Some expressions of traditional contain many teachings, social values, cultural, economic, religiosity, outlook on life, leadership, and even political values, so that the relationship of folklore Bangka language with expressions of folklore is very relevant because some of the culture of a collective that is inherited and passed down through generations. This study aims to describe the value and function of a traditional expression in Bangka community. This study is conducted by ?qualitative descriptive method and techniques of literature and interviews. Bangka traditional expression has a function as a medium to deliver advice, criticism, jokes, prohibition and religion.Keywords: traditional expressions, functions, qualitative descriptive